2018
DOI: 10.1101/343921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detoxification of endogenous serine prevents cell lysis upon glucose depletion in bacteria

Abstract: The amino acid serine, despite its diverse metabolic roles, can become toxic when present in excess. Indeed, many bacteria rapidly deaminate exogenously supplied serine into pyruvate and ammonia, even at the expense of biomass production. Here we report a surprising case in which endogenously produced serine must be detoxified in order for the bacterium Escherichia coli to survive. Specifically, we show that E. coli cells lacking the sdaCB operon, which encodes a serine transporter and a serine deaminase, lyse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…the prokaryotes and isoleucine increased, opposite to what is observed. It has also been reported that high serine levels are toxic [68, 69], possibly contributing to reduced serine levels are reduced in prokaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…the prokaryotes and isoleucine increased, opposite to what is observed. It has also been reported that high serine levels are toxic [68, 69], possibly contributing to reduced serine levels are reduced in prokaryotes.…”
Section: Resultsmentioning
confidence: 99%